Intraoperative Distraction Device for Open Reduction of Nascent Lateral Humeral Condylar Fractures in Five Dogs - Cornell, Jackie D.; Frederick, Steven Walker; Shessel, Blake E.; Cross, Alan R. (VCOT Open, 2023)
Lateral humeral condylar (LHC) nascent malunion fractures are challenging to treat because of extensive callus formation, scar tissue and contracture of surrounding tissues. The objective of this retrospective case series is to describe the novel procedural use of an intraoperative distraction device to aid in the reduction and anatomical alignment of nascent malunion LHC fractures along with long-term functional outcomes in these cases. Medical records of five consecutive cases of dogs with seven nascent malunion LHC fractures that were treated between 2015 and 2018 with the aid of an intraoperative distraction device were reviewed. Relevant clinical and radiographic data, forelimb circumference, elbow goniometry and clinical outcome were evaluated. Anatomic reduction and fixation with complete healing were achieved in all seven cases. Implants were removed in four cases to resolve persisting lameness. Three dogs (4 cases) were available for long-term follow-up: mean circumference and range of motion were decreased in the operated limbs as compared with the contralateral normal limbs. One dog (with bilateral fractures) was euthanized due to poor outcome. In the other five elbows, outcome was acceptable. Based on the results of this case series, use of an intraoperative distraction device to aid in anatomical reduction and fixation of nascent malunion LHC fractures should be considered.
Keywords: humeral condylar fractures; malunion; intraoperative distraction; dog